PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA SAKTI KABUPATEN KERINCI PADA MASA PANDEMI COVID 19 - Sudirman (Bajang Institute, 2023)
This study aims to determine how the influence of the work environment and work motivation on job satisfaction of employees of the Tirta Sakti Regional Public Water Company, Kerinci Regency. The population and sample in this study were 33 employees at the Tirta Sakti Regional Public Water Company, Kerinci Regency. The data analysis tools used are descriptive analysis, multiple linear regression analysis, Coefficient of Determination and hypothesis testing with t test and F test. The results of this study indicate that: There is a significant influence between the work environment on job satisfaction of the employees of the Tirta Sakti Public Water Company. Kerinci Regency, this is evidenced by t count > t table (1.797 > 1.697). There is a significant influence between work motivation on job satisfaction of employees of the Tirta Sakti Regional Public Water Company, Kerinci Regency, this is evidenced by t count > t table (2,394 > 1,697). There is a significant influence between work environment and work motivation on job satisfaction of employees of the Tirta Sakti Regional Public Water Company, Kerinci Regency Simultaneously, which can be proven by F arithmetic > F table (48.511 > 3.32). The magnitude of the influence of the work environment and work motivation on the job satisfaction of the employees of the Tirta Sakti Drinking Water Regional Public Company, Kerinci Regency, is 31.4%. While the remaining 68.6% is explained by other causal factors not examined in this study